CLOCK gene 3’UTR and exon 9 polymorphisms show a strong association with essential hypertension in a North Indian population - Shreya Sopori; Kavinay Kavinay; Sonali Bhan; Shreya Saxena; Medha Medha; Rakesh Kumar; Arti Dhar; Audesh Bhat (BMC Medical Genomics)
Abstract Background Hypertension (HTN) is a medical condition characterized by persistent systolic and diastolic blood pressures of ≥ 140 mmHg and ≥ 90 mmHg, respectively. With more than 1200 million adult patients aged 30–79 years worldwide according to the latest WHO data, HTN is a major health risk factor; more importantly, 46% of patients are unaware of this condition. Essential hypertension (EH), also known as primary hypertension, is the predominant subtype and has a complex etiology that involves both genetic and non-genetic factors. Majority of living organisms are influenced by the light and dark cycle of a day and respond to these changes through an intricate clock referred to as the “biological clock” or “circadian rhythm”. The connection between circadian rhythm and blood pressure is well established, with many studies supporting the role of circadian rhythm gene mutation(s)/polymorphism(s) in EH. To date, no such data are available from any Indian population. Methods This case‒control study was conducted on 405 EH patients and 505 healthy controls belonging to the Jammu region of North India after an informed consent was obtained from the participants. A total of three single nucleotide variants, two in the CLOCK gene (rs1801260 and rs34789226) and one in the BMAL1/ARNTL gene (rs6486121), were selected for genotyping. Genotyping was performed via the RFLP technique, and the applicable statistical analyses were performed via the SPSS and SNPStats programs. Results Logistic regression analysis revealed a statistically significant association of both CLOCK gene variants rs1801260 (T > C 3’UTR) and rs34789226 (C > T Exon 9) and a nonsignificant association of the BMAL1/ARNTL intronic variant rs6486121 (C > T) with EH. The 3’UTR variant showed a statistically significant association under the codominant (p < 0.0001), dominant (p < 0.0001), and recessive (p = 0.0004) models. In contrast, the exon 9 variant showed a statistically significant negative association under the codominant (p = 0.003) and dominant (p = 0.015) models only. The rs6486121/rs1801260 and rs1801260/rs34789226/rs6486121 haplotypes showed significant differences in their distribution between cases and controls (p < 0.0001). Certain genotypes and haplotypes were found more common in hypertensive males than females. Conclusion This is a first report linking circadian rhythm gene polymorphisms with EH in any Indian population. The statistically significant association of the CLOCK gene 3’UTR and exon 9 polymorphisms with EH, highlight the potential role of this gene and probably other genes of the circadian pathway in the etiology of EH in the study population. Additionally, our study also revealed that certain genotypes are making males more susceptible to EH.